Microchip electrophoresis-single wall carbon nanotube press-transferred electrodes for fast and reliable electrochemical sensing of melatonin and its precursors - Gomez, Federico Jose Vicente (2015)
In the current work, single-wall carbon nanotube press-transferred electrodes (SW-PTEs) were used for detection of melatonin (MT) and its precursors tryptophan (Trp) and serotonin (5-HT) on microchip electrophoresis (ME). SW-PTEs were simply fabricated by press transferring a filtered dispersion of single-wall carbon nanotubes on a nonconductive PMMA substrate, where single-wall carbon nanotubes act as exclusive transducers. The coupling of ME–SW-PTEs allowed the fast detection of MT, Trp, and 5-HT in less than 150 s with excellent analytical features. It exhibited an impressive antifouling performance with RSD values of ≤2 and ≤4% for migration times and peak heights, respectively (n = 12). In addition, sample analysis was also investigated by analysis of 5-HT, MT, and Trp in commercial samples obtaining excellent quantitative and reproducible recoveries with values of 96.2 ± 1.8%, 101.3 ± 0.2%, and 95.6 ± 1.2% for 5-HT, MT, and Trp, respectively. The current novel application reveals the analytical power of the press-transfer technology where the fast and reliable determination of MT and its precursors were performed directly on the nanoscale carbon nanotube detectors without the help of any other electrochemical transducer.